ENGARUH PESAN DAKWAH PADA CHANNEL YOUTUBE YUFID.TV TERHADAP MOTIVASI BELAJAR ILMU AGAMA ISLAM - Yori Arfiko; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Online mass media nowadays being a solution for problems to information seeker and more reliable because of the fast information update. The existence of Yufid.TV as youtube Dakwah Channel wich consist of Islam Knowledge studies such as how to worship, doing kindness, social worship, and many others. Theory used in this research is Stimulus - Response Theory. The purpose of this research is to find out how strong the impact of the dakwah message on Yufid.TV Youtube Channel towards motivation of learning Islam knowledge. This research is using Quantitative Research Method, with Online Google Drive or Google Docs given to Yufid.TV Channel subscriber as Data gathering method and 100 total sample which decided by Random Sampling method. Results of this research shows that the impact of dakwah message from youtube channel Yufid.TV towards motivation of learning islam knowledge is moderate or strong enough. This can be seen from the Model Summary Table which shown determination coefficient (R 2 ) is 0,669 and determination coefficient (Rsquare) is 0,447 as the result from squaring correlation coefficient 0,699 x 0,699. These numbers shows that the impact of dakwah message from youtube channel Yufid.TV towards motivation of learning islam knowledge is 44,7%